Avatar, the last airbender. Book 1, Water [videorecording (DVD)] - DiMartino, Michael Dante; Konietzko, Bryan (Paramount, 2015)
"After disappearing for 100 years, Aang has returned to face his destiny as Avatar. And just in the nick of time, as the Four Nations are at war, and the Fire Nation is threatening to take over. Only the Avatar can restore balance, but first, he, along with his friends Katara and Sokka, must begin his journey to master the four elements."--Container.